Faktor-Faktor Yang Mempengarui Minat Kunjungan Wisatawan (Literature Review) - Yandi, Andri; Mahaputra, M. Ridho; Mahaputra, M. Rizky (Siber Nusantara Publisher, 2023)
Abstract: Literature articles reviewing the factors that influence tourists' interest in visiting are scientific articles that aim to build a research hypothesis on the influence of variables to be used in further research, within the scope of management science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Destination image influences tourist interest in visiting; 2) Tourist attractiveness affects the interest of visiting tourists; and 3) Facilities affect the interest of visiting tourists. Apart from these 3 exogenous variables that influence the endogenous variables of interest in visiting tourists there are still many other factors including the variables E-WOM, service quality, price suitability, perception, and convenience. Abstrak: Artikel literatur review faktor-faktor yang mempengaruhi minat berkunjung wisatawan adalah artikel ilmiah yang bertujuan membangun hipotesis riset pengaruh antar variabel yang akan digunakan pada riset selanjutnya, dalam ruang lingkup ilmu manajemen. Metode penulisan artikel Literature Review ini adalah dengan metode library risearch, yang bersumber dari media online seperti Google Scholar, Mendeley dan media online akademik lainnya. Hasil artikel Literature Review ini adalah bahwa: 1) Citra destinasi berpengaruh terhadap minat berkunjung wisatawan; 2) Daya tarik wisata berpengaruh terhadap minat berkunjung wisatawan; dan 3) Fasilitas berpengaruh terhadap minat berkunjung wisatawan. Selain dari 3 variabel exogen ini yang mempengaruhi variabel endogen minat berkunjung wisatawan masih banyak faktor lain di antaranya adalah variabel E-WOM, kualitas pelayanan, kesesuaian harga, persepsi, dan kemuahan.